The Feasibility and Necessity of Holding Elections in Ukraine During the Russian-Ukrainian War: A Legal Analysis - Buchyn, Mykola; Zavada, Yaryna (PRAWO i WIĘŹ, 2025)
This paper explores the legal feasibility and appropriateness of conducting or deferring elections in Ukraine during the ongoing Russian-Ukrainian armed conflict, within the framework of both national legislation and international legal standards. It examines relevant international legal instruments in the field of electoral law, with particular attention to the principles governing the periodicity of elections and the conduct of electoral processes during states of emergency, including armed conflicts. The study further analyzes the legal provisions of Ukrainian domestic law concerning the administration of elections under martial law. The paper argues that, under the current conditions of war, the postponement of presidential and parliamentary elections in Ukraine is consistent with national legislation and does not directly violate international legal obligations concerning electoral rights.